Bridging the Divide: A Multidisciplinary Approach to Developing Climate-Resilient Livelihoods in Coastal Outskirt Areas - Cipta, Hendra (Journal Ligundi of Community Service, 2025)
Background. The increasing vulnerability of coastal outskirt communities to climate change poses serious threats to their livelihoods, economic stability, and cultural heritage. Addressing these issues requires comprehensive and localized strategies that go beyond conventional approaches. Purpose. This multidisciplinary study aimed to develop sustainable and climate-resilient livelihood strategies for marginalized coastal populations by integrating insights from environmental science, social anthropology, economics, and public policy. Method. Field studies, participatory mapping, and community engagement workshops were conducted across selected coastal regions to identify key risks, adaptive capacities, and socio-economic dynamics influencing resilience. The collected data were analyzed qualitatively and quantitatively to formulate an integrated resilience model. Results. The findings highlight the critical role of localized knowledge systems, flexible policy frameworks, and cross-sector collaborations in enhancing community adaptive capacities. Furthermore, the study proposes an integrated model that combines ecosystem-based adaptation, community-led entrepreneurship, and inclusive governance to bridge the gap between scientific innovation and local realities. Conclusion. This research offers practical pathways for policymakers, practitioners, and community leaders to foster sustainable development and improve climate resilience in vulnerable coastal outskirt areas. The proposed model serves as a comprehensive framework to guide future resilience-building initiatives in similar socio-ecological contexts.